«Jag vet inte riktigt vad jag ska göra med svaret…»: En intervjustudie om distriktssköterskors erfarenheter av att samtala med patienter om alkohol. (September 2013) - Jonsson, Åsa; Ottosson, Sandra; Berndtsson, Ina
Background: Nurses should work from health perspective and have profound knowledge of what affects public health. Through dialogue with patients, nurses have an essential role to illustrate patients drinking behavior and illuminate the effects of alcohol on health. Aim: The aim of this study was to illuminate the district nurses experiences of dialogue with patients concerning alcohol. Method: Eight district nurses were interviewed at experiences of dialogue with patients concerning alcohol. Findings: Three themes were interpreted, as feeling of security in reassuring to know that there had time, have sufficient knowledge and to find a good opportunity to talk about alcohol. Personal values attitude affected the dialogue Patient's responsibility for the dialogue when the patient herself not asked at alcohol was it no conversation or if the patient signaled that they did not want to talk about alcohol ended the dialogue. Conclusion: The experience of safety in the work situation, personal attitudes towards alcohol affected the district nurse's attitudes and abilities to accomplish dialogue with patients concerning alcohol. It was remarkable that the responsibility for the content of the dialogue in several occasions was submitted to patients. The district nurses want guidelines and procedures for working with alcohol issues.